World Citizen - Almgren, Eva.; Gustafsson, Evy ([Washington : Distributed by ERIC Clearinghouse, 1974)
The subproject on world citizen responsibility, part of a larger project on social development and training, is summarized. Major objectives of the subproject are the following: (1) to construct, adapt, and test measuring methods to map the social development of student ideas and attitudes to foreign peoples and international relations; (2) to map features of age development; and (3) to explore possibilities for applying educational influence to promote understanding in the world community. Results from the extensive test batteries constructed show that older students have a greater general readiness to make social contacts but have more negative ideas and stereotypes towards minority groups and immigrants. The project compiled an inventory of existing materials for teaching world citizen responsibility, partly by developing and testing new teaching packages. Results of the program tests show that a carefully defined educational influence through such teaching packages can achieve positive effects. (Author/KSM)
Educational level discussed: Elementary Secondary Education.
Educational and Psychological Interactions, n48 Apr 1974.
Microfiche.
Keywords: Age Differences; Reports, Research